An approach to a typology of homicide - Ypsilantis, James Nicholas (1951)
Thesis (M.A.)--Boston University Includes bibliographical references (leaf 54).This study is an analysis of data concerning 240 males convicted of first and second degree murder in the state of Massachusetts during a twenty-five year period, 1925 through 1950. These data were obtained from the files of the Department of Correction for the state of Massachusetts. The study as a whole is an original piece of research work analyzing and classifying the total group into certain experimental typologies in order to get a better understanding of the situations and/or complexes from which the motives for murder arise. The problem is one of discovering and describing certain patterns and uniformities of behavior in these killings. If this paper has accomplished anything it is to indicate that the term "Homocide" is a concept too gross to be utilized in empirical research, that we are dealing with a heterogeneity of phenomena which we term "homocide". [TRUNCATED